CORRELATION OF DEMERIT POINT SCORE (DPS) AND CHEMICAL PARAMETERS ON QUALITY OF FRESH ESTUARY GROUPER (Epinephelus tauvina) DURING STORAGE IN ICE - Farida Ariyani; Yusma Yenni; Rudi Riyanto (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
Quality changes of fresh estuary grouper (Epinephelus tauvina) fish kept in ice was evaluated for sensory and chemical parameters during 21 days of storage. Fish was killed by  immersing in ice water (hypothermia). Fresh fish was placed in insulated boxes, and covered with ice flake. The ratio of ice and fish was 2:1 (w/w) and the boxes were kept at ambient temperature.  Evaluation was conducted every 3 days for sensory characteristics by Demerit Point Score /DPS for appearance, eyes, gills, belly, vent, and belly cavity. Moreover, Total Volatile Base/TVB, Trimethyl Amine/TMA , and the K value were measured until fish was rejected by panelists. The results showed that estuary grouper fish stored in ice was rejected by panelists on 21 days of storage with TVB value of 29.43 mgN%, TMA value of 22.10mgN% and K value of 40.54% (max level of 60%). Related to correlation between sensory and chemical parameters, it showed that Demerit Point Score correlated well with TVB, TMA and K value.